Rapid mapping in Salmonella typhimurium with Mud-P22 prophages. - Benson, N R (1992)
A new method for mapping mutations in the Salmonella typhimurium chromosome is described and applied to the localization of novel regulatory mutations affecting expression of the nirB (nitrite reductase) gene. The mapping technique is also illustrated by the mapping of mutations in genes affecting carbohydrate catabolism and biosynthetic pathways. The new mapping method involves use of the hybrid phage MudP and MudQ (together referred to as Mud-P22), originally constructed by Youderian et al. (Genetics 118:581-592, 1988). This report describes a set of Mud-P22 lysogens, each member of the set containing a different Mud-P22 insertion. The insertions are scattered along the entire Salmonella genome. These lysogens, when induced by mitomycin C, generate transducing lysates that are enriched (45- to 1,400-fold over the background, generalized transducing particle population) for transducing particles containing bacterial DNA that flanks one side of the insertion. We demonstrate that within the set of lysogens there can be found at least one Mud-P22 insertion that enriches for any particular region of the Salmonella chromosome and that, therefore, all regions of the chromosome are discretely enriched and represented by the collection as a whole. We describe a technique that allows the rapid and facile determination of which lysate contains enriched sequences for the repair of a mutant locus, thereby allowing the determination of the map position of the locus. This technique is applicable to those mutations for which the wild-type allele is selectable. We also describe a procedure whereby any Tn10 insertion can be mapped by selecting for the loss of Tetr.